Investigation on a new compact wideband rhombic dielectric resonator antenna. Issue 9 (27th May 2019) - Anoop, P.; Bhattacharjee, Ratnajit
Abstract: In this article, a new rhombic dielectric resonator antenna (DRA) is proposed. Dominant mode and a few of the higher order modes that are excited in this DRA are identified through eigen mode analysis performed through computer simulation technology (CST) simulation. Empirical formulae for calculating the resonant frequency of these identified modes are developed through curve‐fitting approximation. Feeding techniques and possible ways of exciting some of these modes generated in such DRA are also detailed. Investigations are further carried out to identify appropriate feed positions to achieve broadband operation of such DRA geometry. The radiation patterns at different frequencies and variation of gain within the antenna bandwidth are measured for a fabricated prototype and compared with the simulation results.